Notes on the Duirinish Communion Cups - MacLeod, Fred T (Proceedings of the Society of Antiquaries of Scotland, 1923)
This paper is intended as a correction to an earlier published account and relates entirely to the question of who the original donor of the cups was and to which parish the presentation was made. The arms which appear on the cups, including the stag's head, were borne by Sir Rory Mor MacLeod of Dunvegan. They appear on an old gourd or water-bottle which has been in the possession of the MacLeods of Dunvegan from the time of Sir Rory Mor, and is preserved to-day in the castle among the relics of that chief. He received the honour of knighthood in London in the year 1613, the date of the hall-mark on the cups. It is highly probable that on his return to Skye he brought with him the cups for presentation to the parish of Duirinish for the use of the church he worshipped in.